Haludaria, a replacement generic name for Dravidia (Teleostei: Cyprinidae) - Pethiyagoda, Rohan (Zootaxa, 2013)
Pethiyagoda et al. (2012) made available the genus-group name Dravidia (type species Cirrhinus fasciatus Jerdon, 1849: 305) for the ‘Puntius fasciatus’ group of fishes endemic to the peninsula of India. We were unaware at the time this paper was written (2010) that this name had shortly before been preoccupied by Dravidia Lehrer, 2010, in Diptera: Sarcophagidae. As such, a replacement name for this genus of fishes becomes necessary.